Pemanfaatan Sekam Padi Sebagai Energi Alternatif Untuk Membangkitkan Energi Listrik - Marshall V. Supit; Hans Tumaliang; Meita Rumbayan (Universitas Sam Ratulangi, 2015)
Abstract–Electrical energy is one of theinfrastructure related to the livelihood of many people. Until now, the supply of electric energy sources are still reliant on the use of petroleum and coal are expected to be exhausted the next 10-15 years. In this final task, the calculated amount and the potential energy that can be produced from 200 hectares of rice farms in the village Wineru. In the test, the authors made a prototype of a simple steam power plant using rice husk fuel. From burning rice husks 119,75 kg, can be generated by 477.400 kcal of heat energy equivalent to 23,28 kWh of electricity which the combustion efficiency of 93%. Heat energy provided to the working fluid of rice husk power plant prototype average of 32.540,31 kcal. Mechanical energy produced in the turbine of 89,57 kJ/kg equivalent of 24,8 Wh electric energy. The output voltage generator 9 Volt.Electric power that can be generated from 200 hectares of land that is 178,078 kW. Keywords: Alternative Energy, Electrical Energy, Heat Energy, Rice Husk Abstrak– Energi listrik merupakan salah satu infrastruktur yang menyangkut hajat hidup orang banyak. Sampai saat ini, penyediaan sumber energi listrik masih bergantung pada penggunaan minyak bumi dan batu bara yang diperkirakan 10-15 tahun mendatang akan habis. Dalam tugas akhir ini, dihitung jumlah serta potensi energi yang dapat dihasilkan dari 200 hektar lahan pertanian padi di Desa Wineru.Di dalam pengujian, penulis membuat prototype Pembangkit Listrik Tenaga Uap sederhana dengan menggunakan bahan bakar sekam padi. Dari pembakaran sekam padi 119,75 kg, dapat dihasilkan energi kalor sebesar 477.400 kcal setara dengan 23,28 kWh listrik dimana effisiensi pembakaran sebesar 93%. Energi kalor yang diberikan kepada fluida kerja prototype PLTU sekam padi rata-rata 32.540,31 kcal. Energi mekanik yang dihasilkan pada turbin sebesar 89,57 kJ/kg setara 24,8 Wh energi listrik. Tegangan output generator 9 Volt. Energi listrik yang bisa dihasilkan dari 200 hektar lahan yaitu 178,078 kW. Kata Kunci:Energi Alternatif, Energi Kalor, Energi Listrik, Sekam Padi